2016
DOI: 10.1080/03670244.2016.1161617
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of nutrition education: Applying the Health Belief Model in child-feeding practices to use pulses for complementary feeding in Southern Ethiopia

Abstract: Complementary foods (CFs) in Ethiopia are cereal based and adding locally grown pulses (legumes) to CF would provide needed nutrients. To assess the effects of nutrition education (NEd) using Health Belief Model (HBM) in promoting pulses for CF, a 6-month quasi-experimental study was conducted in 160 mother-child pairs. Knowledge, attitude, and practice (KAP) questions were given to mothers at baseline, midline, and endline, along with anthropometric measurements of children. NEd involving discussions and reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(106 citation statements)
references
References 17 publications
7
95
1
1
Order By: Relevance
“…The mean KAP scores in the intervention group are consistent with a study reported from southern Ethiopia which indicated that after six months of pulse nutrition education, the mean knowledge, attitude and practice score of mothers on pulse-incorporated complementary feeding was significantly (p<0.05) improved from 1.09 to 9.46, 2.09 to 9.41 and 1.31 to 7.60 respectively (Mulalem, et al, 2016). In another study, fruit and vegetable consumption, created positive attitude toward healthy foods and may improve academic outcome (Silveira, et al, 2011;Wall, et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The mean KAP scores in the intervention group are consistent with a study reported from southern Ethiopia which indicated that after six months of pulse nutrition education, the mean knowledge, attitude and practice score of mothers on pulse-incorporated complementary feeding was significantly (p<0.05) improved from 1.09 to 9.46, 2.09 to 9.41 and 1.31 to 7.60 respectively (Mulalem, et al, 2016). In another study, fruit and vegetable consumption, created positive attitude toward healthy foods and may improve academic outcome (Silveira, et al, 2011;Wall, et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…Another study conducted in Wolayita zone, southern Ethiopia, the mean (SD) weight for age and weight for height Z-scores of young children were significantly higher in the intervention group compared to those in the control group. The study did not find significant difference in mean (SD) height for age Z-score between the two groups at the end of the pulse nutrition education intervention (Mulalem, et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Recent Demographic Health Survey (EDHS 2011), however, shows a slight decline (stunting 44.4% and underweight 28.7%) for less than 2 years [11], which is still higher than the stunting rate (38%) for less than 5 years in Sub-Saharan Africa [1]. These were not a surprise, as complementary foods in Ethiopia are not optimal and lack nutritional quality, like many other developing countries [4,12].…”
Section: Introductionmentioning
confidence: 89%